Surfing the City via the Web: The Italian Case - Seganti, Francesca Romana (Cyberpsychology: Journal of Psychosocial Research on Cyberspace, 2008)
This article focuses on the Web as an alternative to isolation that often grow in the metropolis because of the loss of communication. It presents part of the results from my research on the social role of an immigrant-oriented online community, Italianialondra.com (IAL). My aim was to detect the role played by the Web in facilitating its members’ integration abroad and in reconstructing communitarian spaces (e.g. home) in London. IAL emerged an exemplar solution for the re-territorialization of London-based Italian immigrants because it is physically de-centered and at the same time it solves local integration problems. What differentiates IAL from other diasporic media is that the places it has helped Italians to be in touch with were in London, just beyond the front door. I conclude that, in any case, its establishment, together with the proliferation of social and business activities and discourses it supports, demonstrates that the experience of the new Italian migrants in London is an empowering one, and therefore, a diaspora ‘in the making’, which does not fit an ideal definition of ‘diaspora’, but is now beginning to assume a distinct character.